Problematika Kinerja Guru Pak Di Dunia Kerja Studi Kasus Pada Guru Pak Smp Negeri Se-Distrik Sentani, Kabupaten Jayapura - Dorce Bu’tu; Riski Tasijawa (Jurnal Pendidikan Indonesia, 2022)
This study stems from the researcher's concern about the education agency's policy that ignores the development of Christian Religious Education teacher competencies through workshops, workshops, and seminars and the teacher's efforts that are not optimal in developing pedagogical, professional, personality, and social abilities in the world of work. The purpose of this study is to analyze the problematic performance of PAK teachers in State Junior High Schools in Sentani District, Jayapura Regency in the world of work. The approach used in this research is descriptive qualitative, while data collection techniques are interviews, observations, and documentation studies. The results showed that PAK teachers at SMP Se-Distrik Sentani Kota have not been optimal in improving pedagogical and professional competencies as support in the world of work. Another finding is that in the aspect of personality and social competence, teachers only focus on the internal school and ignore the external school. The school has not played an optimal role in developing the professional and social competence of PAK teachers through scientific activities of workshops, workshops, and seminars.